A Tribute to Two Master Teachers of Immunology - Roberto Paganelli (Biomedicines, 2023)
A Special Issue dedicated in memory of Prof. Fernando Aiuti is a special tribute to a clinician who led the field of Clinical Immunology in Italy and introduced the entire Italian medical and academic scene to it. [...]